Research and Evaluation of Security Audit Technology in the Era of Network Security Level Protection 2.0. (September 2020) - Li, Zhijie; Suo, Hui
Abstract: With the release of network security level protection 2.0 standard, the work of equal protection evaluation is facing unprecedented challenges. How to deal with it? This paper takes the security audit technology as an example, starting from the concept of network security audit technology, analyzes the security audit object, combines the security audit evaluation index to evaluate the network security equipment, operating system and database system, and puts forward the prospect of security audit evaluation according to the problems in the evaluation practice.